Financing public pensions in Greece - Νεκτάριος Μιλτιάδης (SPOUDAI Journal of Economics and Business, 2000)
The Greek public pensions system is essentially unfunded and it operates on a pay-as-you-go (PAYGO) basis. Serious financial problems are expected after the year 2010, and this is mainly due to adverse demographic trends. The same problem is faced by most European countries. Reform options range between fully funded schemes that will replace PAYGO systems in the long-run, and mixed (two-tier) systems where a basic provision for old age is financed by pay-as you-go and pensions insofar as they exceed this level have to be covered by capital funding. We adopt the second alternative for Greece, and we prove that the proposed two-tier public pension system is actuarially sound for the period 2000-50. Also, it will have positive side-effects on capital formation, and eventually (after 2010-15) will result in a decrease in social insurance contributions. JEL Classification: G 23